Association between vascular risk factors and cognitive impairment in amyotrophic lateral sclerosis: a case-control study. Issue 3 (3rd April 2023) - Yang, Tianmi; Wei, Qianqian; Li, Chunyu; Cao, Bei; Ou, Ruwei; Hou, Yanbing; Zhang, Lingyu; Chen, Yongping; Shang, Huifang
Abstract: Objective: The disease-modifying effects of type 2 diabetes mellitus (T2DM), and hyperlipidemia on the risk and prognosis of amyotrophic lateral sclerosis (ALS) have gained significant attention. We aim to evaluate the association between common vascular risk factors and cognitive impairment in patients with ALS. Methods: Patients with ALS were consecutively recruited between June 2012 and November 2019 from a tertiary referral center for ALS at the West China Hospital. Vascular risk factors (hypertension, T2DM, hyperlipidemia, overweight, and smoking) were confirmed based on clinical data. Cognitive function was evaluated by the Chinese version of Addenbrooke's Cognitive Examination-revised. With careful confounder adjustment, multivariable logistic regression analysis was performed separately and accumulatively to determine the association between cognitive impairment and vascular risk factors in ALS. Results: Of 870 patients, 266 (30.6%) had cognitive impairment. No cognitive burden from vascular risk factors was found in patients with ALS. On the contrary, we first observed that T2DM (odds ratio [OR], 0.50; 95% confidence interval [CI], 0.25–0.98; p  = 0.04) and hyperlipidemia (OR, 0.50; 95% CI, 0.26–0.97; p  = 0.04) showed protective effects against cognitive decline in ALS, adjusted for age, sex, educational level, site of onset, Revised-ALS Functional Rating Scale score, predominant upper motor neuron phenotype, family history of ALS, and the remaining vascular risk factors. Sensitivity analyses of sex did not substantially reverse the risk estimates. Conclusions: T2DM and hyperlipidemia decrease the risk of cognitive impairment in patients with ALS. The fitness hypothesis in ALS has been tested and expanded in our work.